Antimicrobial peptides: basics for clinical application - Matsuzaki, Katsumi (Advances in experimental medicine and biology, 2019)
Part 1. Introduction -- Chapter 1. Antimicrobial peptides of multicellular organisms: My perspective -- Part 2. Mechanisms of Antimicrobial Action -- Chapter 2. Membrane permeabilization mechanisms -- Chapter 3. Elementary processes and mechanisms of interactions of antimicrobial peptides with membranes --- single GUV studies ---- -- Chapter 4. The mechanisms of action of cationic antimicrobial peptides refined by novel concepts from biophysical investigations -- Chapter 5. Anionic lipid clustering model -- Chapter 6. Intracellular antimicrobial peptides targeting the protein synthesis machinery -- Part 3. Other activities of AMPs -- Chapter 7. Antimicrobial and cell-penetrating peptides: How to understand two distinct functions despite similar physicochemical properties -- Chapter 8. Synthetic anti-lipopolysaccharide peptides (SALP) as effective inhibitors of pathogen-associated molecular patterns (PAMPs) -- Chapter 9. Anti-cancer activities of natural and synthetic peptides -- Chapter 10. Antimicrobial host defence peptides: Immunomodulatory functions and translational prospects -- Part 4. Towards Clinical Applications -- Chapter 11. Activity and selectivity of antimicrobial peptides: A complex interplay of multiple equilibria -- Chapter 12. Design of antimicrobial peptides: Progress made with human cathelicidin LL-37 -- Chapter 13. Application of synthetic molecular evolution to the discovery of antimicrobial peptides -- Chapter 14. AMPs as anti-biofilm agents for human therapy and prophylaxis -- Chapter 15. Clinical application of AMPs